Assessment of nutritional status, dietary intake and adherence to dietary recommendations in type 1 diabetic children and adolescents - Sanaa El-Jamal; Houda Elfane; Hamid Chamlal; Khadija Sahel; Imane Barakat; Mohamed Mziwira; Aziz Fassouane; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Currently, T1D is one of the most common chronic diseases in children and adolescents. The International Diabetes Federation (IDF) estimates that more than 1.1 million children and adolescents are living with (T1D). A few studies have evaluated the relationship between dietary intake and glycemic control (GC) in people with T1D, and in particular, children and adolescents. Objective. The aim of this study was to evaluate the relationship between anthropometric characteristics, lipid profile, inflammation, dietary intake and GC in comparison with international guidelines. Materials and methods. The study included a sample of 240 children, aged 15 years old or less with T1D. A structured questionnaire was used to collect information on the socio-demographic status, disease characteristics, and diet of the participants. Weight, height, and WC were measured and WHtR and BMI were calculated. Biochemical measurements were determined. Dietary intake was assessed using three 24-hour recalls. Results. Saturated fat intake was five times higher than recommended. Only 8.3% of participants reached the recommended level of fiber. Overweight, obesity, TC, TG, HDL and CRP were significantly higher in children with poor GC to those with good GC. In addition, participants with poor GC had significantly low intakes of calories, carbohydrates, fiber, MUFAs, and PUFAs and high intakes of fat and SFAs. The use of Bivariate correlation analyses showed that calorie, protein, fat and fiber intake were positively correlated with weight, height, WC, and GO, whereas carbohydrate intake was negatively associated with these parameters. On the contrary, CO showed a negative correlation with calorie, protein, fat and fiber intake and a positive correlation with carbohydrate intake. Conclusions. The results revealed that the dietary quality was poor and adherence to dietary recommendations was low with insufficient fiber intake and excess SFA. These results suggest that GC can be improved by a healthy, balanced diet by increasing fiber intake and limiting SFA intake.